1984
DOI: 10.1161/01.cir.69.6.1142
|View full text |Cite
|
Sign up to set email alerts
|

Immediate hemodynamic effects of a dopamine-receptor agonist (fenoldopam) in patients with essential hypertension.

Abstract: Systemic, splanchnic, and renal hemodynamics, intravascular volume, and reflexive and endocrine changes were measured before and after a single dose of fenoldopam, a novel antihypertensive agent that acts through stimulation of specific dopamine receptors. A 13% reduction in mean arterial pressure was mediated by a fall in total peripheral resistance associated with an increase in cardiac index, heart rate, stroke volume, left ventricular ejection rate, and circumferential fiber shortening. Renal blood flow in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
30
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 17 publications
7
30
0
Order By: Relevance
“…This study confirms and extends previous studies that have demonstrated the antihypertensive efficacy of fenoldopam, both after oral'8-21 and, especially, intravenous1314, 17,19,[22][23][24][25] have shown that intravenous fenoldopam is effective in mild-to-moderate hypertension,14 refractory hypertension (i.e., patients with diastolic blood pressures >115 mm Hg on triple-drug therapy),23 and severe hypertension,172425 but this is the first series to include a majority of patients with accelerated/ malignant hypertension, which is presumably the population in which it will find the widest use. In addition, the present series includes a preponderance of black patients, who comprise a small minority of those previously treated with fenoldopam.17 Indeed, because of the greater frequency of severe hypertension and its complications (including accelerated/malignant hypertension) in blacks,26'27 fenoldopam may be especially useful in such patients, who more commonly have reduced salt and water excretion rates,28 independent of the degree of renal dysfunction.…”
Section: Discussionsupporting
confidence: 91%
“…This study confirms and extends previous studies that have demonstrated the antihypertensive efficacy of fenoldopam, both after oral'8-21 and, especially, intravenous1314, 17,19,[22][23][24][25] have shown that intravenous fenoldopam is effective in mild-to-moderate hypertension,14 refractory hypertension (i.e., patients with diastolic blood pressures >115 mm Hg on triple-drug therapy),23 and severe hypertension,172425 but this is the first series to include a majority of patients with accelerated/ malignant hypertension, which is presumably the population in which it will find the widest use. In addition, the present series includes a preponderance of black patients, who comprise a small minority of those previously treated with fenoldopam.17 Indeed, because of the greater frequency of severe hypertension and its complications (including accelerated/malignant hypertension) in blacks,26'27 fenoldopam may be especially useful in such patients, who more commonly have reduced salt and water excretion rates,28 independent of the degree of renal dysfunction.…”
Section: Discussionsupporting
confidence: 91%
“…Increments in HR previously have been observed with orally administered fenoldopam in hypertensive patients. 23 ' 24 Furthermore, in a recent study, we observed that intravenous infusions of fenoldopam in hypertensive patients consistently increased plasma NE levels. 23 Although piribedil is used primarily as a centrally acting DA agonist for the treatment of Parkinson's disease, 26 it also inhibits adrenergic transmission by action on DA 2 receptors.…”
Section: Discussionmentioning
confidence: 75%
“…23 ' 24 Furthermore, in a recent study, we observed that intravenous infusions of fenoldopam in hypertensive patients consistently increased plasma NE levels. 23 Although piribedil is used primarily as a centrally acting DA agonist for the treatment of Parkinson's disease, 26 it also inhibits adrenergic transmission by action on DA 2 receptors. 18 In the present study, the hypotensive effects of piribedil were completely blocked by domperidone, whereas the bradycardie effect was significantly but not completely antagonized.…”
Section: Discussionmentioning
confidence: 75%
“…Fenoldopam, a potent agonist at peripheral dopamine1 (DA1)-receptors, has been shown to produce beneficial haemodynamic effects including an improvement in renal plasma flow and a reduction in blood pressure following both intravenous and oral administration (Stote et al, 1983;Ventura et al, 1984). The development of this benzazepine derivative followed the elucidation of the role of dopamine in the regulation of vascular tone and blood pressure (Stoof & Kebabian, 1984;Yeh et al, 1969; Leenders et al, 1984;Langer, 1974 it does not produce such effects in the intact animal because of poor penetration across the blood-brain barrier (Harvey et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…These effects began approximately 45 min after dosing and persisted for 2-3 h. While mean heart rate increased modestly, mean blood pressure was relatively unchanged in these normal subjects. However, in hypertensive patients, fenoldopam is associated with a significant antihypertensive effect (Ventura et al, 1984).…”
Section: Introductionmentioning
confidence: 99%